Elder Financial Abuse Experience: A Qualitative Study from the Perspective of Older Persons in Malaysia - Nurfadhilah Che Amani; Rojanah Kahar; Rahimah Ibrahim; Muslihah Hasbullah (Human Resource Management Academic Research Society, 2024)
Indexed by ERA